An overview of selected material properties in finite element modeling of the human femur - Pourya Bazyar and Andreas Baumgart and Holm Altenbach and Anna Usbeck (Biomechanics, 2023)
Specific finite detail modeling of the human body gives a capable primary enhancement to the prediction of damage risk through automobile impact. Currently, car crash protection countermeasure improvement is based on an aggregate of testing with installed anthropomorphic test devices (i.e., ATD or dummy) and a mixture of multibody (dummy) and finite element detail (vehicle) modeling. If an incredibly easy finite element detail version can be advanced to capture extra statistics beyond the abilities of the multi-body structures, it might allow advanced countermeasure improvement through a more targeted prediction of overall performance. Numerous research has been done on finite element analysis of broken femurs. However, there are two missing pieces of information: 1- choosing the right material properties, and 2- designing a precise model including the inner structure of the bone. In this research, most of the chosen material properties for femur bone will be discussed and evaluated.
Keywords: femur; material; isotropic; anisotropic; orthotropic